Haemodynamic profile of the potassium channel activator EMD 52692 in anaesthetized pigs. - Sassen, L. M. (1990)
1. The systemic and regional haemodynamic effects of the potassium channel activator EMD 52692 or its solvent were investigated after intravenous and after intracoronary administration in anaesthetized pigs. 2. Consecutive intravenous 10 min infusions of EMD 52692 (0.15, 0.30, 0.60, 1.20 micrograms kg-1 min-1; n = 7) dose-dependently decreased mean arterial blood pressure by up to 50%. This was entirely due to peripheral vasodilatation, since cardiac output did not change. Heart rate increased by up to 50%, while left ventricular end diastolic pressure decreased dose-dependently from 6 +/- 1 mmHg to 3 +/- 1 mmHg (P less than 0.05), and stroke volume decreased from 30 +/- 2 ml to 21 +/- 2 ml (P less than 0.05). Left ventricular dP/dtmax was not affected. 3. Although cardiac output did not change, EMD 52692 caused a redistribution of blood flow from the arteriovenous anastomoses to the capillary channels. Blood flow to the adrenals, small intestine, stomach, bladder, spleen and brain increased, while renal blood flow decreased and blood flow to several muscle groups and skin were not altered. Vascular conductance was increased dose-dependently in all organs, except for the kidneys, where after the initial increase, vascular conductance returned to baseline with the highest dose. Particularly striking were the effects on the vasculature of the brain. With the highest dose of EMD 52692 blood flow more than doubled, while vascular conductance increased four fold. 4. Transmural myocardial blood flow increased slightly, which was entirely due to an increase in subepicardial blood flow. Myocardial O2-consumption and segment length shortening were not significantly affected. 5. After consecutive 10 min intracoronary infusions (0.0095, 0.019, 0.0375 and 0.075 microgram kg-1 min-1; n = 7) into the left anterior descending coronary artery (LADCA), mean arterial blood pressure was maintained with the lowest two doses, but decreased by up to 15% with the higher doses, whereas heart rate increased by up to 24%. Blood flow to the LADCA-perfused myocardium doubled with the highest dose, the subepicardium benefitting the most. Coronary venous O2-saturation increased dose-dependently from 23 +/- 2% to 60 +/- 4%, while myocardial O2-consumption of the LADCA-perfused myocardium was not affected by the drug. 6. It is concluded that EMD 52692 is a potent vasodilator, with particularly pronounced effects on vasculature of the brain.(ABSTRACT TRUNCATED AT 400 WORDS)